1946
DOI: 10.1172/jci101696
|View full text |Cite
|
Sign up to set email alerts
|

Blood Volume in Clinical Shock. Ii. The Extent and Cause of Blood Volume Reduction in Traumatic, Hemorrhagic, and Burn Shock12

Abstract: found evidence of a direct relation between the severity of shock and the extent of the reduction in blood volume. This has been clearly demonstrated in recent experimental studies on traumatic and hemorrhagic shock in dogs (4, 5) in which blood volume was determined with more dependable methods. Within the past two years, there have also been reports of similar observations on cases of shock among civilians (6, 7, 8, and others).The aim of the present investigation was: (1) to determine more precisely the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1946
1946
2013
2013

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…This is in accord with recent reports that the hematocrit and plasma protein values are below normal before treatment in shock cases among civilian and war casualties (4,25). From our experience also it appears that in cases of skeletal trauma and hemorrhage, uncomplicated by exposure or dehydration, the initial determinations of hematocrit and plasma protein after the injury fall below the average normal values (3,10). Evidence of hemoconcentration has been observed only in the cases of burns and abdominal injuries, which, as noted above, provide the only clear instances of increased disappearance of dye.…”
Section: -Minute Samplesmentioning
confidence: 53%
See 1 more Smart Citation
“…This is in accord with recent reports that the hematocrit and plasma protein values are below normal before treatment in shock cases among civilian and war casualties (4,25). From our experience also it appears that in cases of skeletal trauma and hemorrhage, uncomplicated by exposure or dehydration, the initial determinations of hematocrit and plasma protein after the injury fall below the average normal values (3,10). Evidence of hemoconcentration has been observed only in the cases of burns and abdominal injuries, which, as noted above, provide the only clear instances of increased disappearance of dye.…”
Section: -Minute Samplesmentioning
confidence: 53%
“…The general plan was, (1) to make a systematic study of time-concentration curves of T-1824 in patients with various types of injuries and degrees of shock in order to evaluate the effect of shock on the time of mixing and disappearance rate of the dye, and to define the extent to which these factors influence the measurement of plasma volume in shock-like states; (2) to determine the extent and, if possible, the cause of blood volume reduction in human cases of shock. The results of the latter phase of the investigation are presented in a separate communication (10).…”
mentioning
confidence: 99%
“…Since then especially the classic investigations of the English (GRANT and REEVE [553]) and of the American shock teams of World War II (BEECHER et al [114,115]; EMERSON [411]) and of the Korean War (ARTz et al [78]; HOWARD [730]) have shown that the main cause of hemorrhagic and traumatic shock [1090] is to be found in the reduction of the circulating BV [423], and that restoration of the BV by means of sufficient blood transfusion can relieve shock if the hypovolemic phase does not remain untreated for too long (survey in REEVE [1167]). …”
Section: The Volume Effect Of Blood Transfusions -Therapeutic Resmentioning
confidence: 99%
“…In the experiments reported in [28], recovery following haemorrhage occurred for a mean loss of 34.5% of total blood volume while a 43% blood loss was progressive. In [29,30], clinical signs of progressive shock occur with a blood loss in the range of 30 -40% of total blood volume. Consistent with these measured data, in the present simulation a 30% blood loss results in a minimum arterial pressure of 54 mmHg and, from figure 10, recovery is predicted.…”
Section: The Representations For Both Anso and Cnso In The Present Momentioning
confidence: 99%